Curso de Bacharelado em Ciências Militares: reconstrução do percurso sócio-histórico, análise da concepção pedagógica e perspectivas - Paola Bonanato Lopes (2011)
The Military Police of Minas Gerais (PMMG) has several roles within the context of confrontation with crime, in the Public Security scenario. One of these roles concerns the qualifications and technical skills of its members, which are considered essential in the modern police professional philosophy based on serving and protecting people. In PMMG there are two possibilities for admission, one through a Technician Course (CTSP) and another from a graduation course (CBCM). The object of the present study is related to the last one, and intends to research the police officers education who are professionals responsible for managing the public security in Minas Gerais state. The CBCM, which originated from the course named Curso de Formação de Oficiais (CFO), began in 1934. Since then, it has been adapted to the demands of different ages, and it has followed professional evolution. In accordance with the socio-educational panorama of the late twentieth century supported by sustainability and peace search and the democratic state of law, emerged guidelines from the federal government due to the need for qualification and restructure of the professional training of public security. In PMMG, the process that has been developed since then, culminated in the recognition of the Academy of Military Police (APM) as an Institution of Higher Education with the graduation course named Bachelor Course of Military Sciences (CBCM), approved by the State Board of Education. This research led to the socio-historical construction of the course. Political, social and situational aspects were identified as well as influenced such construction. The process which was developed in order to achieve recognition was slow and gradual and it took about 10 years from the first discussions to its effectiveness. No. 450/2003 rule from the State Board of Education technical and educational parameters were used as a reference. At the same time, a pedagogical concept was unveiled from the analysis of educational documents and narrative interviews conducted with professionals who took part of the course development. This pedagogical concept used Demerval Saviani as a reference. This author considers the philosophical, theoretical and practical as dimensions of a pedagogical concept. Philippe Perrenoud, Guy Le Boterf and Donald Schön were authors used to support the concept of competence, which subsidizes the CBCM pedagogical proposal. The analyzed documents show the intention to work on the competence theory model which focus on theory-practice link, reflexivity and autonomy that foster meaningful learning. The same documents, however, together with interviews, show that there is inconsistency between the prescribed theory and the factual practice. That is, the pedagogical concept of the CBCM is described, but there are obstacles to its realization. Some potential obstacles pointed out in this study might be the socialization process into military culture and its practices, the construction of professional identity, organizational values, the lack of technical training for officers who work with the Education of Military Police Education and the lack of a permanent faculty.